(untitled) (Research, Society and Development, 2024)
An inherent consequence after tooth extraction is the resorption of the alveolar bone, especially that of the buccal bone plate, which leads to a height and width reduction of the alveolar ridge. This aesthetically affects the rehabilitation, and serves as a major challenge in implant dentistry. Several techniques were developed with the goal of containing this resorption, such as immediate implant, bone graft and accelerated tissue regeneration through the use of membranes. However, a more recent alternative called Socket Shield Technique (SST) has demonstrated very promising results, namely the unique capacity of buccal bone plate preservation, which optimizes the aesthetic aspect of the rehabilitation. It consists in retention of a buccal segment of the root in the alveolus, acting as a shield for the implant. The goal of this study is to describe a case report with the use of the SST, associated with the installation of an implant in the area pertaining to unit 21, of a patient with indication for extraction of this unit and implant rehabilitation, due to fracture on the middle third of the tooth. After 7 months, the definitive restoration was made and with a 10 months total proservation, no alteration that indicated functional or aesthetic failure was observed. Results found by this case demonstrates the potential of the SST, however, more studies of higher academic relevance and longer follow-up time must be developed, so that the efficiency of this technique can be truly verified, especially concerning long-term results.